Protective Role of Probiotic Supplements in Hepatic Steatosis: A Rat Model Study. (23rd November 2020) - Azarang, Aein; Farshad, Omid; Ommati, Mohammad Mehdi; Jamshidzadeh, Akram; Heidari, Reza; Abootalebi, Seyedeh Narjes; Gholami, Ahmad
Abstract : Background . Treating nonalcoholic fatty liver disease (NAFLD) is considered one of the public health priorities in the past decade. So far, probiotics have represented promising results in controlling the signs and symptoms of NAFLD. However, attempts to find the ideal probiotic strain are still ongoing. The present study is designed to find the best strain amongst suitable probiotic strains according to their ability to ameliorate histopathological and oxidative stress biomarkers in hepatic steatosis-induced rats. Methods . Initially, four probiotics species, including Lactobacillus ( L. ) acidophilus, L. casei, L. reuteri, and Bacillus coagulans, were cultured and prepared as a lyophilized powder for animals. The experiment lasted for fifty days. Initially, hepatic steatosis was induced by excessive ingestion of D-fructose in rats for eight weeks, followed by eight weeks of administering probiotics and D-fructose concurrently. Forty-two six-week-old male rats were alienated to different groups and were supplemented with different probiotics (1 ∗ 10 9 CFU in 500 mL drinking water). After eight weeks, blood and liver samples were taken for further evaluation, and plasma and oxidative stress markers corresponding to liver injuries were examined. Results . Administration of probiotics over eight weeks reversed hepatic and blood triglyceride concentration and blood glucose levels. Also, probiotics significantly suppressed markers of oxidative stress in the liver tissue. Conclusions . Although some of the single probiotic formulations were able to mitigate oxidative stress markers, mixtures of probiotics significantly ameliorated more symptoms in the NAFLD animals. This enhanced effect might be due to probiotics' cumulative potential to maintain oxidative stress and deliver improved lipid profiles, liver function markers, and inflammatory markers.